PROTECTING WOMEN AND CHILDREN DURING FAMILY LITIGATION: A COMPARATIVE STUDY OF TEMPORARY ALIMONY IN MIDDLE EASTERN FAMILY LAWS - Muhammad Nasrulloh; Faridatus Suhadak; Muhammad Faiq; Abdul Haris (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Temporary alimony has emerged as an important mechanism for protecting women and children from economic hardship during ongoing family litigation. However, Indonesian family law has yet to establish a clear legal framework governing temporary alimony, creating a gap in legal protection before a final court judgment is rendered. This study addresses the question of how temporary alimony mechanisms in selected Middle Eastern jurisdictions can inform the reform of Indonesian family law. Employing a normative legal method, the research uses statutory, conceptual, and comparative approaches, with legal materials analyzed through a descriptive- comparative framework. The findings show that Egypt, Kuwait, Bahrain, Oman, Libya, Syria, and the United Arab Emirates have developed temporary alimony mechanisms through interlocutory decisions that are immediately enforceable and possess direct executorial force. Two principal typologies are identified: temporary alimony limited to maintenance disputes and temporary alimony applicable to broader family law cases. These regulations reflect a shift in contemporary family law from a formalistic dispute-resolution model toward a preventive legal protection framework that safeguards women and children against economic, social, and psychological vulnerability during litigation. In contrast, Indonesian family law continues to treat maintenance primarily as a consequence of a final judgment, leaving a significant protection gap throughout the judicial process. This study argues that adopting a temporary alimony mechanism is essential for strengthening legal protection for women and children in Indonesia and for advancing a more responsive, gender-just, and maqāṣid al-sharīʿah-oriented family law system. Keywords: temporary alimony, family law, women and children protection, middle eastern countries.